Главная

Алгебра 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебрее 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г.

Раздел:

Номер №637

Найдите корень уравнения:
а)
$1 - \frac{x - 3}{2} = \frac{2 - x}{3} + 4$
;
б)
$\frac{a + 13}{10} - \frac{2a}{5} = \frac{3 - a}{15} + \frac{a}{2}$
;
в)
$\frac{2m + 1}{4} + 3 = \frac{m}{6} - \frac{6 - m}{12}$
;
г)
$\frac{x + 1}{9} - \frac{x - 1}{6} = 2 - \frac{x + 3}{2}$
.

Решение а

$1 - \frac{x - 3}{2} = \frac{2 - x}{3} + 4$
|*6
63(x − 3) = 2(2 − x) + 24
63x + 9 = 42x + 24
3x + 2x = 2869
−x = 13
x = −13

Решение б

$\frac{a + 13}{10} - \frac{2a}{5} = \frac{3 - a}{15} + \frac{a}{2}$
|*30
3(a + 13) − 12a = 2(3 − a) + 15a
3a + 3912a = 62a + 15a
9a + 2a − 15a = 639
22a = −33
$a = \frac{33}{22} = \frac{3}{2}$

a = 1,5

Решение в

$\frac{2m + 1}{4} + 3 = \frac{m}{6} - \frac{6 - m}{12}$
|*12
3(2m + 1) + 36 = 2m − (6 − m)
6m + 3 + 36 = 2m − 6 + m
6m − 3m = −639
3m = −45
m = −45 : 3
m = −15

Решение г

$\frac{x + 1}{9} - \frac{x - 1}{6} = 2 - \frac{x + 3}{2}$
|*18
2(x + 1) − 3(x − 1) = 369(x + 3)
2x + 23x + 3 = 369x − 27
−x + 9x = 923
8x = 4
x = 4 : 8
x = 0,5